FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA SEKTOR PARIWISATA DI JAWA TIMUR TAHUN 2014-2020 - Susanti, Meiliana Setefany Ayu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The tourism sector is one of the sectors that contributes to the growth of the Indonesian economy, particularly in terms of job creation, resulting in employment absorption. This study aims to analyze the influence of the tourism sector on employment absorption in five regencies/cities in East Java Province from 2014 to 2020. The analysis method used in this study is panel data regression analysis. Employment in the tourism sector is determined as the dependent variable, while the number of tourists, the number of hotels, and the minimum wage act as independent variables. The research findings conclude that the number of tourists has a significant negative effect, the number of hotels has a non-significant positive effect, and the minimum wage has a significant positive effect on employment absorption.